Morphoarchitectural variation in South African fossil cercopithecoid endocasts. Issue 101 (December 2016) - Beaudet, Amélie; Dumoncel, Jean; de Beer, Frikkie; Duployer, Benjamin; Durrleman, Stanley; Gilissen, Emmanuel; Hoffman, Jakobus; Tenailleau, Christophe; Thackeray, John Francis; Braga, José
Abstract: Despite the abundance of well-preserved crania and natural endocasts in the South African Plio-Pleistocene cercopithecoid record, which provide direct information relevant to the evolution of their endocranial characteristics, few studies have attempted to characterize patterns of external brain morphology in this highly successful primate Superfamily. The availability of non-destructive penetrating radiation imaging systems, together with recently developed computer-based analytical tools, allow for high resolution virtual imaging and modeling of the endocranial casts and thus disclose new perspectives in comparative paleoneurology. Here, we use X-ray microtomographic-based 3D virtual imaging and quantitative analyses to investigate the endocranial organization of 14 cercopithecoid specimens from the South African sites of Makapansgat, Sterkfontein, Swartkrans, and Taung. We present the first detailed comparative description of the external neuroanatomies that characterize these Plio-Pleistocene primates. Along with reconstruction of endocranial volumes, we combine a semi-automatic technique for extracting the neocortical sulcal pattern together with a landmark-free surface deformation method to investigate topographic differences in morphostructural organization. Besides providing and comparing for the first time endocranial volume estimates of extinct Plio-Pleistocene South African cercopithecoid taxa, we report additional information regarding the variation in the sulcal pattern of Theropithecus oswaldi subspecies, and notably of the central sulcus, and the neuroanatomical condition of the colobine taxon Cercopithecoides williamsi, suggested to be similar for some aspects to the papionin pattern, and discuss potential phylogenetic and taxonomic implications. Further research in virtual paleoneurology, applied to specimens from a wider geographic area, is needed to clarify the polarity, intensity, and timing of cortical surface evolution in cercopithecoid lineages.